Uwarunkowania procesu podejmowania decyzji w agrobiznesie - Nesterowicz, Renata; Kawa, Marta (Conditions of Undertaking Decisions in Agribusiness, 2005)
This paper presents the way of undertaking decisions by farmers. Principle of market economy and Poland - EU integration process influence the conditions of undertaking decisions. The most problematic is instability of market circumstances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 119-124